2023
DOI: 10.3390/ijerph20010843
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Use and the Associated Factors among Women of Reproductive Age in Jazan City, Saudi Arabia: A Cross-Sectional Survey

Abstract: The contraceptive use profile is poorly understood in some Gulf Arabian countries, including Saudi Arabia. The present study aimed to assess the knowledge, attitude, and practices related to contraceptive use among women of childbearing age in Jazan city, Saudi Arabia. An observational, analytical cross-sectional study was conducted among a random sample of 450 women in Jazan city. The data were obtained through personal interviews using a questionnaire that included questions on women’s level of knowledge abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…The current study found that 80.25% of the participants have used any form of contraception; this estimate is roughly in line with a cross-sectional study carried out in Hail City (85%) in 2020 [29], but it is slightly higher than those in Jazan in 2018 (64.4%) [30], Taif in 2015 (67.7%) [11], and Jeddah in 2018 (69.7%) [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study found that 80.25% of the participants have used any form of contraception; this estimate is roughly in line with a cross-sectional study carried out in Hail City (85%) in 2020 [29], but it is slightly higher than those in Jazan in 2018 (64.4%) [30], Taif in 2015 (67.7%) [11], and Jeddah in 2018 (69.7%) [13].…”
Section: Discussionsupporting
confidence: 90%
“…The utilization of contraception was similar in these Saudi areas due to the similarities in the participants' socio-economic characteristics. The main reason for using contraceptives in this study is child spacing (35.96%); this finding is supported by the researchers in Jazan in 2018 [ 30 ]. Contraceptive pills were the most widely used method of birth control, followed by intrauterine devices (28.97%).…”
Section: Discussionsupporting
confidence: 81%
“…Healthcare facilities must offer family planning counseling and health education initiatives to increase awareness and use of contraceptive techniques. To make greater use of the available family planning services, contraception awareness campaigns should also be made available to men (Mahfouz et al, 2023).…”
Section: Level Of Knowledge On Different Contraceptives Among Indigen...mentioning
confidence: 99%
“…The study emphasizes the value of DOH local health clinics to women of reproductive age as a resource for knowledge and access to contraceptive options. The World Health Organization (WHO) asserts that ensuring women's access to chosen contraceptive methods is crucial for promoting both the community's economic well-being and the health of mothers and children (Mahfouz et al, 2023).…”
Section: The Prevalence Of Contraceptive Use Among Indigenous Womenmentioning
confidence: 99%
“…Oral contraceptive pills (OCP) are the most commonly used contraceptive measure, owing to their effectiveness and practicability. [1] The estimated use of OCPs ranges from 45% to 64% in the Kingdom of Saudi Arabia [2].…”
Section: Introductionmentioning
confidence: 99%